Teaching medical students about communication in speech-language disorders: Effects of a lecture and a workshop. (1st November 2016) - Saldert, Charlotta; Forsgren, Emma; Hartelius, Lena
Abstract: Purpose : This study aims to explore the effects of an interactive workshop involving speech-language pathology students on medical students' knowledge about communication in relation to speech-language disorders. Method : Fifty-nine medical students received a lecture about speech-language disorders. Twenty-six of them also participated in a workshop on communication with patients with speech-language disorders. All students completed a 12-item questionnaire exploring knowledge and attitudes towards communication before and after the lecture or the workshop. The results from the two groups' self-ratings of confidence in knowledge were compared with expert-ratings of their ability to choose suitable communicative strategies. Result : Both the lecture and the workshop increased the students' confidence in knowledge about speech-language disorders and how to support communication. Only the workshop group also displayed a statistically significant increase in expert-rated ability and changed their attitude regarding responsibility for the communication in cases of speech-language disorders. There were no statistically significant correlations between the student's own confidence ratings and the experts' ratings of ability. Conclusion : Increased confidence in knowledge from learning is not always reflected in actual knowledge in how to communicate. However, an interactive workshop proved to increase medical students' expert-rated ability and attitudes related to communication in cases of speech-language disorders.